Electronic Structures and Chiroptical Properties of Post‐functionalized Helicene Quinones. Issue 21 (23rd April 2016) - Schweinfurth, David; Mazzolini, Marcella; Neshchadin, Dmytro; Hoyer, Carolin; Geier, Roman; Gatterer, Karl; Trapp, Nils; Gescheidt, Georg; Diederich, François
Abstract: The synthesis of redox‐active p ‐ and o ‐quinones 2‐phenylamino‐4‐phenylimino[6]helicene‐1‐one1, 2‐phenylamino[6]‐helicene‐1, 4‐dione2, and 4‐phenyl[6]helicene‐1, 2‐dione3 in their enantiopure forms by post‐functionalization of ( P )‐ and ( M )‐1, 2‐dimethoxy[6]helicene is presented. Structural characterization in solution and in the solid state was accomplished by 2D NMR spectroscopy methods and X‐ray diffraction analysis, respectively. Interpretation of electrochemical redox data was accompanied by a detailed orbital picture, derived from DFT calculations. The electronic structures of compounds1 –3 were investigated by UV/Vis and electronic circular dichroism (ECD) spectroscopy, complemented by TD‐DFT calculations. Quinones1 –3 were chemically reduced to study the EPR signatures of their respective radical anions. DFT methods were used for the atom assignment of the hyperfine coupling constants. The results are discussed within the context of electrochromic chiral switches and molecular recognition. Abstract : Let's get curly : Post‐functionalization reactions of helicenes are presented that allowed for the synthesis of redox‐active helicene o ‐ and p ‐quinones (see figure). UV/Vis, ECD, and EPR spectroscopy, electrochemical analysis, and DFT calculations were used to reveal structure–property relationships.